Measuring website service quality of Malaysian companies / Voon Boo Ho, Karen Kueh Meng Koon and Mohd Zafian Mohd Zawawi - Boo Ho, Voon; Kueh, Karen Meng Koon; Mohd Zawawi, Mohd Zafian (2009)
Customer-perceived service quality is essential for enhancing customer satisfaction and loyalty. This is-also true for online services, particularly in view-of-the increasing-use-of websites as a channel for information presentation and provision of other services. Hence, the website service quality perceptions of users need to be understood so as to manage it more effectively. In this survey research, the key dimensions for website service quality were identified through qualitative and quantitative approaches. The website quality theories, focus groups and survey results were used for generating the numerous dimensions and items for understanding and measuring website service quality of selected Malaysian companies from the users' perspective.